Systematic review and meta-analysis of interventions to increase the uptake of vaccines recommended during pregnancy - Annette K. Regan; Honorine Uwimana; Stacey L. Rowe; Elizabeth Jitka Olsanska; Brianna Agnew; Eliana Castillo; Alice Fiddian-Green; Michelle L. Giles (npj Vaccines)
Abstract Although immunization during pregnancy can protect mothers and their infants from vaccine-preventable morbidity and mortality, vaccination rates are often poor. We systematically reviewed the literature from inception to July 4, 2023, for randomized and non-randomized quasi-experimental studies estimating the effects of interventions to increase vaccination during pregnancy. Of 9331 studies screened, 36 met inclusion criteria, including 18 demand-side interventions, 11 supply-side interventions, and seven multi-level (demand and supply-side) interventions. Demand-side interventions commonly addressed patient education, showing modest improvement (pooled RR 1.18; 95% CI: 1.04, 1.33; I 2 = 63.1%, low certainty). Supply-side interventions commonly implemented Assessment-Feedback-Incentive-eXchange interventions with little improvement (pooled RR 1.13; 95% CI: 0.96, 1.33; I 2 = 94.0%, low certainty). Multi-level interventions were modestly effective in increasing vaccination (pooled RR 1.62; 95% CI: 1.09, 2.42; I 2 = 97%, very low certainty). Interventions identified in the literature mostly resulted in low to moderate increases in vaccination with likely high heterogeneity and low to very low certainty in the findings.